The Legal and Economic Principles of World Trade Law: National Treatment - Gene M. Grossman; Henrik Horn; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2012)
The purpose of the study is to propose interpretations of the National Treatment (NT) provision included in Art. III GATT, unbound by case-law interpretations of this provision. To make such proposals, we need to understand the role of the provision in the agreement. To this end, we first examine in Chapter 2 the negotiating record relevant to the rationale for the enactment of this provision, as well as the manner in which case law has understood it. In the same Chapter, we also discuss the role of NT in the General Agreement on Tariffs and Trade (GATT) from the perspective of economic theory. Having established the purpose of NT, we discuss in Chapter 3 the manner in which this provision has been implemented in case law: that is, here we focus on the understanding of the key terms implementing the purpose of NT by GATT and World Trade Organization (WTO) adjudicating bodies. At the end of this Chapter we provide a critical assessment of the case law. In light of our dissatisfaction with the case-law interpretations of some key terms, we present in Chapter 4 our preferred interpretation of NT.
Keywords: F13; 330; National treatment; Trade agreement; WTO; GATT; Most favoured nation; WTO-Regeln; Incoterms; Außenwirtschaftsrecht